Precise repair of mPing excision sites is facilitated by target site duplication derived microhomology. Issue 1 (December 2015) - Gilbert, David; Bridges, M.; Strother, Ashley; Burckhalter, Courtney; Burnette, James; Hancock, C.
Abstract Background A key difference between theTourist andStowaway families of miniature inverted repeat transposable elements (MITEs) is the manner in which their excision alters the genome. Upon excision, Stowaway -like MITEs and the associatedMariner elements usually leave behind a small duplication and short sequences from the end of the element. These small insertions or deletions known as "footprints" can potentially disrupt coding or regulatory sequences. In contrast, Tourist -like MITEs and the associatedPIF/Pong /Harbinger elements generally excise precisely, returning the genome to its original state. The purpose of this study was to determine the mechanisms underlying these excision differences, including the role of the host DNA repair mechanisms. Results The transposition of theTourist -like element, mPing, and theStowaway -like element, 14T32, were evaluated using yeast transposition assays. Assays performed in yeast strains lacking non-homologous end joining (NHEJ) enzymes indicated that the excision sites of both elements were primarily repaired by NHEJ. Altering the target site duplication (TSD) sequences that flank these elements reduced the transposition frequency. Using yeast strains with the ability to repair the excision site by homologous repair showed that some TSD changes disrupt excision of the element. Changing the ends ofmPing to produce non-matching TSDs drastically reduced repair of the excision site and resulted in increased generation of footprints. Conclusions Together these results indicate that the difference inTourist andStowaway excision sites results from transposition mechanism characteristics. The TSDs of both elements play a role in element excision, but only themPing TSDs actively participate in excision site repair. Our data suggests thatTourist -like elements excise with staggered cleavage of the TSDs, which provides microhomology that facilitates precise repair. This slight modification in the transposition mechanism results in more efficient repair of the double stranded break, and thus, may be less harmful to host genomes by disrupting fewer genes.